Autoburlesque - A Parasite in the Nation’s Body: On Lea Aini’s Writing - Ronen, Irit (MiKAN, 2016)
How is it that author Lea Aini burst into public awareness and penetrated the heart of Hebrew literature particularly through her novel The Rose of Lebanon (2009)? Following a pluralistic trend and a desire to expose suppressed, exotic and colorful marginal stories, critics expected Aini to provide autobiographical stories that uncover life at the social and ethnic margins. Aini has published many novels and short stories, while rejecting the critics’ demands. When she finally complied, she did so in a disruptive, ‘indecent’ manner: by distorting the language, dismantling the great symbols of the renewed Hebrew culture, and using autobiography, the founding genre of the national ethos, while undermining it at the same time, converting it into a wild hybrid, which I have termed ‘autoburlesque’. Contrary to the common view of literary critics, according to which Lea Aini expresses in her work a latent aspiration to be accepted into the center of the cultural milieu, the article argues that through artistic cunningness, Aini threatens to alter this center and make it redundant, in a way that is similar to the tactics applied by a parasite to its host. The article considers Aini’s works published prior to The Rose of Lebanon, and aims to explain how they challenged the conventions of the socio-political discourse, and why The Rose of Lebanon did ultimately turn into a kind of magnum opus and succeed in penetrating the heart of the canon.